2006
DOI: 10.1007/s10339-006-0097-z
|View full text |Cite
|
Sign up to set email alerts
|

Visuo-spatial pseudohemineglect in professional sportsmen

Abstract: Repetition behavior such that involved in some professional circumstances (e.g., sport or musical training) seems to generate consistent and relatively typical changes, as a consequence of cerebral plasticity. We comparatively examined, independently for each hand, the performances in a line bisection task of three equivalent (in respect to relevant demographic parameters) groups of male subjects, all right-handed: professional sportsmen in branches requiring eye-hand coordination (n = 27), students in sports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Considering that most Chinese people are trained to use their right hands as artful ones in their early lives 25, studies of such training in athletes showed consistently moderate rightward errors in the line bisection task 26,27, we therefore selected 155 moderate to strong right-handed subjects for our study. Fifty-six healthy volunteers were recruited among college students, medical staff members or paid volunteers.…”
Section: Methodsmentioning
confidence: 99%
“…Considering that most Chinese people are trained to use their right hands as artful ones in their early lives 25, studies of such training in athletes showed consistently moderate rightward errors in the line bisection task 26,27, we therefore selected 155 moderate to strong right-handed subjects for our study. Fifty-six healthy volunteers were recruited among college students, medical staff members or paid volunteers.…”
Section: Methodsmentioning
confidence: 99%